Industrial agglomeration, international R&D capital and air pollution-based on provincial spatial panel data - Gao, Dawei; Deng, Yan; Chen, Zhengyang (Frontiers in Environmental Science, 2024)
This paper presents a spatial effect model to examine the impact of industrial agglomeration and international R&D capital technology spillover on air pollution. The study utilizes spatial panel data from 30 provinces and cities in China spanning the period 2008 to 2022, allowing for the decomposition of both direct and indirect spillover effects.Additionally, the research investigates the threshold effect of industrial agglomeration and international research and development capital and technology spillover on air pollution, considering independent research and development as the threshold variable. The findings reveal evident spatial autocorrelation and spatial dependence between industrial agglomeration, international R&D capital, and air pollution. Importantly, both international R&D capital technology spillover and industrial agglomeration exhibit a single threshold effect. This implies that surpassing the threshold value leads to a more pronounced positive impact of international R&D capital technology spillover on reducing air pollution, while the impact of industrial agglomeration on air pollution tends to be positive. The findings of this study have significant theoretical and practical implications for the promotion of sustainable economic development, particularly in China.